2012
DOI: 10.1007/s11738-012-1107-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ascorbic acid and gibberellin A3 on alleviation of salt stress in common bean (Phaseolus vulgaris L.) seedlings

Abstract: Salinity, a severe environmental factor, has limited the growth and productivity of crops. Many compounds have been applied to minimize the harmful effects of salt stress on plant growth. An experiment was conducted to investigate the interactive effects of exogenous ascorbic acid (AsA) and gibberellic acid (GA 3 ) on common bean (Phaseolus vulgaris L. cv. Naz) seedlings under salt stress. The changes of growth parameters, photosynthetic and non-photosynthetic pigments and potassium content showed that the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 54 publications
(81 reference statements)
7
49
1
2
Order By: Relevance
“…2 A&B). Additionally, ASC protects chloroplasts from oxidative damage by stimulating IAA and GA 3 synthesis and by inhibiting ABA formation (Saeidi-Sar et al, 2013;Gul et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…2 A&B). Additionally, ASC protects chloroplasts from oxidative damage by stimulating IAA and GA 3 synthesis and by inhibiting ABA formation (Saeidi-Sar et al, 2013;Gul et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its pool size may serve as an underlying mechanism in plant protection against photoinhibition, especially under stress conditions. It has been reported that the exogenously supplemented ascorbate in plants exposed to abiotic stressors had a vital impact on the prevention of lipid peroxidation and the restoration of the plasma membrane (Bai et al, 2013;Saeidi-Sar et al, 2013).…”
Section: Photosynthetic Pigmentsmentioning
confidence: 99%
“…The regulating role of Se on the uptake and redistribution of some essential elements like S, Zn, Mn, Cu, and Fe, especially the latter, is introduced as a key mechanism to stimulate the antioxidant system, decrease the levels of reactive oxygen species, and enhance chlorophyll biosynthesis pathways, thereby improving plant resistance to stress (Feng et al, 2013). Considering the pivotal roles of ascorbate and GSH metabolites in antioxidant defenses (Noctor and Foyer, 1998), these compounds play an important role in the protection against oxidative damage under abiotic stress (Bai et al, 2013;Gallie, 2013;Saeidi-Sar et al, 2013).…”
Section: The Antioxidative System and Antioxidant Activities (Free Ramentioning
confidence: 99%
“…In contrast, GPX activity prominently increased respectively at 12 and 24h after GA 3 treatment relative to control (Figure 4). Evidences exist that confirm increase in antioxidant enzyme activities under GA treatment, especially in various stressful conditions [20][21][22].…”
Section: Gpx and Apx Enzyme Activity And Total Proteinmentioning
confidence: 99%